Design and rationale of the MyHeartMate study: a randomised controlled trial of a game-based app to promote behaviour change in patients with cardiovascular disease. Issue 5 (14th May 2019) - Gallagher, Robyn; Chow, Clara; Parker, Helen; Neubeck, Lis; Celermajer, David; Redfern, Julie; Tofler, Geoffrey; Buckley, Thomas; Schumacher, Tracy; Ferry, Cate; Whitley, Alexandra; Chen, Lily; et al.
Abstract : Introduction: Recurrence of cardiac events is common after a first event, leading to hospitalisations and increased health burden. Patients have difficulties achieving the lifestyle changes required for secondary prevention and access to secondary prevention programs is limited. This study aims to evaluate the impact of a game-based mobile app, MyHeartMate, which is designed to motivate engagement in secondary prevention behaviours for cardiovascular risk factors. Methods and analysis: The MyHeartMate study is a randomised controlled trial with 6-month follow-up and blinded assessment of the primary outcome. Participants (n=394) with coronary heart disease will be recruited from hospitals in metropolitan Sydney and randomly allocated to standard care or the MyHeartMate app intervention. The intervention group will receive the app, which uses game techniques to promote engagement and lifestyle behaviour change for secondary prevention. The primary outcome is difference between the groups in physical activity (metabolic equivalent of task minutes/week) at 6 months. Secondary outcomes include change in low-density lipoprotein cholesterol, systolic blood pressure, medication adherence, body mass index, waist circumference, mood and dietary changes at 6 months. Data on app engagement, and patient perspectives of usability and acceptability, will also be analysed. Ethics and dissemination: The study has received ethics approval from Northern Sydney Local Health District Human Research Ethics Committee. The study findings will be disseminated via peer-reviewed publications and presentation at international scientific meetings/conferences. Trial registration number: ACTRN12617000869370; Pre-results.